Արևմտահայության կացությունը և հայ հասարակական միտքը օսմանյան բարենորոգչական շարժման համատեքստում (XIX դ. 70-ական թվականներ) - Գևորգ Հարությունյան (ՀՀ ԳԱԱ հրատ.)
В 60-70-х годах XIX в. Турция была отсталой аграрной страной. Тяжелому экономическому положению Османской империи соответствовала создавшаяся в стране политическая ситуация. Крымская война усугубила социально-экономический кризис, финансовая зависимость Турции от европейского капитала грозила колонизацией страны. In the 60s-70s of the 19th c. Turkey was a law-developed agricultural country. The hard economic condition of the Ottoman Empire corresponded to the political situation of the state. The Crimean war worsened the social – economic crisis, and financial dependence of the European capital threated colonization of the state.
Keywords: History; D History